USE OF GLP-1 RECEPTOR AGONISTS IN THE TREATMENT OF OBESITY: CLINICAL EVIDENCE AND NUTRITIONAL IMPLICATIONS (REMUNOM, 2025)
Obesity is a chronic condition that is difficult to manage, requiring therapeutic strategies that go beyond invasive interventions. The emergence of glucagon-like peptide-1 (GLP-1) receptor agonists and dual agonists (GIP/GLP-1) has established a new paradigm in the pharmacological treatment of obesity, achieving weight loss ranging from 15% to 30%, which, in certain contexts, is comparable to outcomes observed after bariatric surgery. This study aimed to analyze the efficacy and metabolic impacts of semaglutide and tirzepatide, with an emphasis on challenges related to therapeutic adherence and clinical safety. This is a literature review, which indicates that despite high clinical efficacy, the use of these medications is associated with frequent gastrointestinal adverse effects, such as nausea and constipation, as well as relevant risks of nutritional deficiencies, particularly in the absence of adequate monitoring. The most commonly reported deficiencies include minerals such as iron, calcium, and magnesium, as well as B-complex vitamins and fat-soluble vitamins (A, D, E, and K). It is concluded that therapeutic success depends on a multidisciplinary approach integrating pharmacotherapy with nutritional monitoring and regular physical exercise, aiming to preserve lean mass and ensure the long-term sustainability of caloric deficit.